Pengelolaan Sumber Daya Manusia di Rintisan Sekolah Menengah Atas Bertaraf Internasional Majlis Tafsir Al-Qur’an (R-SMA-BI MTA) Surakarta - Ihlas; Sukrin; Aris Munandar (Journal of Education and Teaching (JET), 2020)
This research examines the Human Resource Management in Senior High School of International Standard Majlis Tafsir Al-Qur'an Surakarta. This research is a qualitative-ethnographic research that produces descriptive data. This was done at R-SMABI MTA Surakarta, Central Java. This study is a qualitative study with ethnography focusing on culture, planning, placement and / or development and evaluation of Human Resources (HR). The goal is to explore the management and development model of human resources in R-SMA-BI MTA Surakarta. The findings of this study are: First, the culture is conducive. Second, HR planning that is tailored to the needs analysis with the important needs of a Muslim, and other supportive conditions. Third, some human resource placements do not meet academic qualifications and competencies. Meanwhile, the qualifications of human resources have not met the R-SMA-BI standards. For the health and welfare of human resources it has also been regulated. Third, the evaluation conducted by the government and schools using various models.